1990
DOI: 10.1007/bf00164071
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive consequences of male cooperation in the red howler monkey: paternity exclusion in multi-male and single-male troops using genetic markers

Abstract: Variance in male reproductive success in single and multi-male red howler (Alouatta seniculus) troops was examined through paternity exclusion using genetic markers. Coalitions of relatives were compared to coalitions of non-relatives with regard to duration, stability, and number of offspring expected for each participant based on paternity exclusion results. No evidence of paternity by males living outside of the troop was found. In multi-male troops, only the dominant male was found to father offspring conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
160
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(173 citation statements)
references
References 22 publications
7
160
0
1
Order By: Relevance
“…In this situation, it was predicted and observed that within-group male coalitions would be directed towards extra-group males and function to reduce male group size (Pope, 1990;Dias et al, 2010;Berghänel et al, 2010). However, data from one of our groups shows high reproductive skew in favor of the alpha male.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…In this situation, it was predicted and observed that within-group male coalitions would be directed towards extra-group males and function to reduce male group size (Pope, 1990;Dias et al, 2010;Berghänel et al, 2010). However, data from one of our groups shows high reproductive skew in favor of the alpha male.…”
Section: Discussionmentioning
confidence: 69%
“…Groups with more females and species where female receptivity is temporally concentrated are more likely to show multi-male groupings because a single male cannot monopolize many females (Nunn, 1999;Cords, 2000). In a typical uni-male, multi-female system, multi-male groups may form due to male influxes, attempted takeovers by single males where the resident male remains in the group, takeovers by coalitions of extra-group males, or when males remain in their natal group past maturity creating age-graded groups (Dunbar, 1984;Pope, 1990;Sicotte, 1993;Cords, 2000;Sterck & van Hooff, 2000;Watts, 2000b;Dias et al, 2010). When males are able to co-reside in these types of multimale groups, male relationships may vary from simple mutual tolerance to the formation of strong affiliative bonds, which may include within-group coalitions against conspecifics, potentially with a preference for certain partners over others (Mitchell, 1994;van Hooff & van Schaik, 1994;Olson & Blumstein, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations